2006
DOI: 10.1097/01.jcp.0000219051.40632.d5
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-blind, Placebo-controlled Study of Citalopram in Adolescents With Major Depressive Disorder

Abstract: In a European, multicenter, double-blind study, 244 adolescents, 13 to 18 years old, with major depression were randomized to treatment with citalopram (n = 124) or placebo (n = 120). One third of the patients in both groups withdrew from the study. No significant differences in improvement of scores from baseline to week 12 between citalopram and placebo were found. The response rate was 59% to 61% in both groups according to the Schedule for Affective Disorders and Schizophrenia for school-aged children-Pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(36 citation statements)
references
References 19 publications
0
33
0
3
Order By: Relevance
“…However, concerns about suicidal risk were prevalent before the Wagner et al article was written and published [27]. In fact, undisclosed in both the published article and Wagner's letter-to-the-editor, the 2001 negative Lundbeck study had raised concern over heightened suicide risk [10,20,21].…”
Section: Mischaracterisation Of Adverse Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, concerns about suicidal risk were prevalent before the Wagner et al article was written and published [27]. In fact, undisclosed in both the published article and Wagner's letter-to-the-editor, the 2001 negative Lundbeck study had raised concern over heightened suicide risk [10,20,21].…”
Section: Mischaracterisation Of Adverse Eventsmentioning
confidence: 99%
“…Even though the results of a prior European citalopram pediatric registration trial (i.e., Lundbeck study 94404) were not published until 2006 [21], as early as July 16, 2001, Forest was aware that the Lundbeck study had failed to demonstrate efficacy for citalopram in adolescents [22]. However, Wagner et al omitted this fact in their published article, leading the editors of the American Journal of Psychiatry to publish a correction, acknowledging that Forest had failed to disclose the result that the Lundbeck trial was negative and had shown an increase in suicidality in both children and adolescents [19].…”
Section: Ms Prescott Writes: "I Don't Know That Any Decision Has Beementioning
confidence: 99%
“…We did not use data from either the Hamilton Depression Rating Scale [19] or the Montgomery-Asberg Depression Rating Scale [20] because these measures were designed for use in adults and may not be ideal to assess depressive severity in youth. Data reporting in one study was quite minimal [21]. For this study, we extracted mean change data on the Kiddie Schedule for Affective Disorders and Schizophrenia from a figure in the paper, in which it was clear that the mean difference between groups was zero.…”
Section: Methodsmentioning
confidence: 99%
“…For the Beck Depression Inventory (BDI), we calculated the standard deviation in von Knorring et al [21] as the sample size-weighted standard deviation from Berard et al [22] and Emslie et al [58]. For the Kiddie Schedule for Affective Disorders and Schizophrenia, we calculated the standard deviation in von Knorring et al [21] as the sample size-weighted standard deviation from Berard et al [22] and Keller et al [23]. …”
Section: Methodsmentioning
confidence: 99%
“…In an 8-week, flexible-dose, placebo-controlled study of MDD in children and adolescents (7-17 years of age), racemic citalopram 20-40 mg/day demonstrated significant improvement in depressive symptoms versus placebo within 1 week . In subsequent clinical trials of citalopram (age range, 13-18 years) (von Knorring et al 2006) and escitalopram (age range, 6-17 years) (Wagner et al 2006), active treatment failed to separate from placebo. However, age-group adjusted post-hoc analyses of the escitalopram trial (Wagner et al 2006) revealed significant differences in favor of escitalopram compared with placebo in the adolescent subgroup (age range, 12-17 years).…”
Section: Introductionmentioning
confidence: 99%